Inactivation of antibiotic-resistant bacteria Escherichia coli by electroporation - Haberl Meglič, Saša; Slokar, Dejan; Miklavčič, Damijan (Frontiers in Microbiology, 2024)
In modern times, bacterial infections have become a growing problem in the medical community due to the emergence of antibiotic-resistant bacteria. In fact, the overuse and improper disposal of antibiotics have led to bacterial resistance and the presence of such bacteria in wastewater. Therefore, it is critical to develop effective strategies for dealing with antibiotic-resistant bacteria in wastewater. Electroporation has been found to be one of the most promising complementary techniques for bacterial inactivation because it is effective against a wide range of bacteria, is non-chemical and is highly optimizable. Many studies have demonstrated electroporation-assisted inactivation of bacteria, but rarely have clinical antibiotics or bacteria resistant to these antibiotics been used in the study. Therefore, the motivation for our study was to use a treatment regimen that combines antibiotics and electroporation to inactivate antibiotic-resistant bacteria. We separately combined two antibiotics (tetracycline and chloramphenicol) to which the bacteria are resistant (with a different resistance mode) and electric pulses. We used three different concentrations of antibiotics (40, 80 and 150 µg/ml for tetracycline and 100, 500 and 2000 µg/ml for chloramphenicol, respectively) and four different electric field strengths (5, 10, 15 and 20 kV/cm) for electroporation. Our results show that electroporation effectively enhances the effect of antibiotics and inactivates antibiotic-resistant bacteria. The inactivation rate for tetracycline or chloramphenicol was found to be different and to increase with the strength of the pulsed electric field and/or the concentration of the antibiotic. In addition, we show that electroporation has a longer lasting effect (up to 24 hours), making bacteria vulnerable for a considerable time. The present work provides new insights into the use of electroporation to inactivate antibiotic-resistant bacteria in the aquatic environment.